2017
DOI: 10.1088/1478-3975/aa5ee7
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the ion-coupling mechanism in the MATE transporter NorM-VC

Abstract: Bacteria have developed a variety of different mechanisms to defend themselves from compounds that are toxic to them, such as antibiotics. One of these defence mechanisms is the expulsion of drugs or other noxious compounds by multidrug efflux pumps. Multidrug and toxic compound extrusion (MATE) transporters are efflux pumps that extrude metabolic waste and a variety of antibiotics out of the cell, using an ion gradient as energy source. They function via an alternative-access mechanism. When ions bind in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…The fact is, however, that neither Rb + nor Cs + actually mimics Na + in any respect other than its charge. Indeed, a recent simulation study of outward-facing NorM-VC where the bound Rb + was replaced by Na + showed the ion to be stable only when an inward 400-mV electrostatic potential was applied across the protein (40). Evidently, that a membrane potential be present (chemical or electrostatic) is not a requirement for ion or substrate binding to secondary-active transporters (consider, for example, binding assays for purified, detergent-solubilized protein, or crystal structures).…”
Section: Resultsmentioning
confidence: 99%
“…The fact is, however, that neither Rb + nor Cs + actually mimics Na + in any respect other than its charge. Indeed, a recent simulation study of outward-facing NorM-VC where the bound Rb + was replaced by Na + showed the ion to be stable only when an inward 400-mV electrostatic potential was applied across the protein (40). Evidently, that a membrane potential be present (chemical or electrostatic) is not a requirement for ion or substrate binding to secondary-active transporters (consider, for example, binding assays for purified, detergent-solubilized protein, or crystal structures).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown recently that the N-lobe and the C-lobe ion binding sites from the sodium coupled MATE transporter NorM-VC [21,27] and NorM-NG [22] are solvent accessible, which is a prerequisite for ion binding and release, as e.g. discussed for the ion translocation mechanism of the membrane embedded domain from V-type ATPases [46], which is able to close the luminal water channel and thus prevents proton transport [47] to inactivate the enzyme.…”
Section: Water Accessibility Of the Internal Cavity Of Clbmmentioning
confidence: 99%
“…Initially, the MATE transporter NorM from Vibrio cholerae (NorM-VC) was suggested to be coupled to sodium ions and protons [9], with the proton and sodium predicted to be harbored within the same binding site [27]. In contrast, recent measurements of ligand binding to NorM-VC indicated that the binding site residues solely coordinate protons [28]; however the authors of this study also claimed that a two-fold shift in the EC 50 (Na + ) for the E255Q mutant was observed, which indicates ion binding to E255 at some point during the conformational transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Distinct interactions of these macromolecules with ligands and water molecules determine their structure and function, as in e. g. opening of ion‐channels upon binding of signaling molecules at the solvent accessible surface of the protein, or the folding of proteins and RNA, which is crucial for key activities such as enzyme catalysis. In addition, the recognition of ligands, including e. g. ions in soluble and membrane embedded proteins, small organic molecules, or even other macromolecules such as proteins, RNA and DNA can be governed by structural water molecules. Water access to a ligand binding site may be required in order for ligands to bind or exit; e. g. protons cannot be released from the V‐type ATPase if the protein channel is closed preventing water accessibility .…”
Section: Introductionmentioning
confidence: 99%